Validação da assimilação de dados na inferência da refletividade de um radar com sistema MM5 - Silva, Gustavo Leite da (2009)
On certain occasions the State of Rio Grande do Sul is affected by atypical weather systems events which are among the category of mesoscale phenomena. The inability of large scale numerical models to appropriately simulate several localized effects, which occurs over the most varied regions, associated to the fast increase of computational resources, it is facilitating and increasingly inducing the use of mesoscale models to improve the knowledge on those anomalous and severe events and even for use as a necessary and indispensable operational tool. The skill of mesoescala model to proceed in providing precipitation forecasts, in space and time scale compatible with to those of a Doppler meteorological radar, it is implemented the whole system of mesoscale modeling that constitutes the MM5. The occurrence of the relatively severe precipitation event, in the area close to the city of Canguçu / RS, on January 11, 2008 was arbitrarily selected to evaluate the model skill - in inferring the reflectivity of the meteorological radar, installed in Canguçu / RS proceeding with conventional data assimilations, PCA (Processing With Assimilation) and PSA (Processing Without Assimilation), as well an approach to the analysis of the thermo-hydrodynamics and synoptic conditions.